Біологічні особливості та географічне поширення Neottia nidus-avis (L.) Rich. (Orchidaceae Juss.) у Закарпатті - Loya, V.V.; Gaponenko, M.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The paper deals with the biological features and geographical distribution of Neottia nidus-avis (L.) Rich. (Orchidaceae Juss.) in Transcarpathia. It is an palaearctic species growing in Ukraine on south-east border of its range.